Pemphigus vegetans successfully treated with systemic corticosteroid and rituximab: a rare case report with 15-month follow-up and literature review - Ji, Hongyan; Chen, Liuqing; Chen, Jinbo (Frontiers in Immunology, 2026)
Pemphigus vegetans (PVeg) is a rare variant of pemphigus vulgaris characterized by pustules and/or vegetating plaques, preferentially affecting the flexural areas. The diagnosis of PVeg depends on clinical grounds, histopathology, and direct immunofluorescence. Systemic corticosteroid is the first-line therapy for PVeg, and immunosuppressive treatments such as azathioprine, mycophenolate mofetil, and intravenous immunoglobulins can be used to improve remission rates. Also, there have been a few reports on the use of rituximab for treating PVeg. Here, we present a rare case of PVeg successfully treated by rituximab and provide the first brief review of the application of rituximab in PVeg. Additionally, this patient experienced muscle weakness after treatment but gradually improved with tapering prednisone, which increased our understanding of steroid myopathy.